Opioid crisis: Should Malaysia be worried? - Zin, Che Suraya (2019)
About 20 years ago, compassionate advocacy for better treatment of chronic pain, combined with aggressive marketing of opioid formulations, led to a sharp increase in the prescribing of opioid analgesics for patients with chronic noncancer pain (CNCP) in most developed countries. An unintended consequence of this approach was an “opioid epidemic” in the United States, namely an increase in opioid use and in parallel misuse/abuse and deaths. Every day, more than 130 people in the United States die after overdosing on opioids. The misuse of and addiction to opioids including prescription pain relievers, heroin, and synthetic opioids is a serious national crisis that affects public health as well as social and economic welfare.